2018
DOI: 10.5604/01.3001.0012.0736
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the best microstructure and titanium alloy powders properties using neural network

Abstract: Purpose: Create a software product using a probabilistic neural network (PNN) and database based on experimental research of titanium alloys to definition of the best microstructure and properties of aerospace components. Design/methodology/approach: The database creation process for artificial neural network training was preceded by the investigation of the granulometric composition of the titanium powder alloys, study of microstructure, phase composition and evaluation of micromechanical properties of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 20 publications
1
11
0
Order By: Relevance
“…For modeling of the proposed methods, it was used the DataSet from [8,9]. Based on the studies from [8,25], it was possible to distinguish four groups of characteristics that effect a composition of an alloy, which can be synthesized from four different titanium alloys powder components (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For modeling of the proposed methods, it was used the DataSet from [8,9]. Based on the studies from [8,25], it was possible to distinguish four groups of characteristics that effect a composition of an alloy, which can be synthesized from four different titanium alloys powder components (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…1), which are characteristic of this task, sometimes lead to an ineffective solution of the task, in particular by tools of computing intelligence [19]. In [8], the solution accuracy of the classification task (on the same data as in the work) using the Probabilistic Neural Network was 70%.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…of artificial intelligence [9,10] increases the efficiency of the procedure for developing or designing new materials. Traditional approaches allow obtaining all necessary information about the material properties [7], and the usage of powerful [11], modern ML algorithms [12][13] makes this process easier, shorter and cheaper.…”
Section: на основі експериментально встановлених даних щодо параметріmentioning
confidence: 99%
“…Artificial intelligence tools can be used to reduce the duration, as well the cost of investigation of the properties of spherical and nonspherical titanium alloy powders [10]. The conducted literature review has shown the feasibility of using the algorithms of machine learning to solve this task, in particular on the basis of the Random Forest algorithm and the Kolmogorov-Gabor polynomial.…”
Section: Investigation Of the Materials Propertiesmentioning
confidence: 99%